Sinha Vitória: olhares e dizeres - Cassamassimo, Maria Elisa (2010)
This study was focused in the work Vidas Secas (2006), and the object of our research is the character Sinha Vitória. Our proposal seeks, in a way, supply in the fortune criticism of the novel, the absence of studies that bring into focus the feminine character in greater depth, to open a new perspective on reflexive Sinha Vitória and her transforming function in the course of the narrative. For that, we starting with these questions: how can we say that Sinha Vitória is the one who lives the internal world of the other characters, leading and giving force to them? In what way her projective look and her progressive language acquisition (starting at guttural sounds to a real articulated speech) are the responsables for her capacity in lead all the family? What is the real meaning of this feminine character in Vidas Secas? So, our hypothesis is that Sinha Vitória is structured under a principle in which their dialogical self awareness is defined by otherness, dialog with its own conscience and the other characters, especially with Fabiano; and that is she who provides in the work a liberating action of the cycle of drought, by means of self awareness founded on two pillars: the eye projective-imaginative and speech, whose transformation of guttural sounds until the speech articulated. This feminine character is, in our point of view, the strengh who moves this research, whose purpose is to understand the roots of a character built under the principle dialogical that is founded on the "look" and the "say". The theoretical foundations focused on several conceptions about the look contained in the work O Olhar (1998), organized by Adauto Novaes, and in Bakhtin´s theories about the dialogism and indirect free speech, specially in his works Marxismo e Filosofia da Linguagem (1999) and Questões de Literatura e de Estética (1998). This study presents Sinha Vitória´s projective look, whose strengh is able to make, in the speech, other new dialogical spaces